Metabolically healthy general and abdominal obesity are associated with increased risk of hypertension. Issue 5 (3rd December 2019) - Zhao, Yang; Qin, Pei; Sun, Haohang; Liu, Yu; Liu, Dechen; Zhou, Qionggui; Guo, Chunmei; Li, Quanman; Tian, Gang; Wu, Xiaoyan; Hu, Dongsheng; Sun, Xizhuo; et al.
Abstract: Metabolically healthy obesity refers to a subset of obese people with a normal metabolic profile. We aimed to explore the association between metabolically healthy and obesity status and risk of hypertension among Chinese adults from The Rural Chinese Cohort Study. This prospective cohort study enrolled 9137 Chinese adults without hypertension, type 2 diabetes or treatment for lipid abnormality at baseline (2007–2008) and followed up during 2013–2014. Modified Poisson regression models were used to examine the risk of hypertension by different metabolically healthy and obesity status, estimating relative risks (RR) and 95 % CI. During 6 years of follow-up, we identified 1734 new hypertension cases (721 men). After adjusting for age, sex, smoking and other confounding factors, risk of hypertension was increased with metabolically healthy general obesity (MHGO) defined by BMI (RR 1·75, 95 % CI 1·02, 3·00) and metabolically healthy abdominal obesity (MHAO) defined by waist circumference (RR 1·51, 95 % CI 1·12, 2·04) as compared with metabolically healthy non-obesity. The associations between metabolically healthy and obesity status and hypertension outcome were consistent after stratifying by sex, age, smoking, alcohol drinking and physical activity. Both MHGO and MHAO were associated with increased risk of hypertension. Obesity control programmes should be implemented to prevent or delay the development of hypertension in rural China.